Breastfeeding Duration and Adolescent Educational Outcomes: Longitudinal Evidence From India. Issue 4 (December 2017) - Nandi, Arindam; Lutter, Randall; Laxminarayan, Ramanan
Objective: There is a significant evidence gap on the long-term educational benefits of longer breastfeeding in low- and middle-income countries. We estimated the association between duration of (any) breastfeeding and educational outcomes of Indian children. Methods: We used regression analysis to examine the association between the length of breastfeeding (in months) and future education outcomes on the basis of 2 data sets: (1) data from a follow-up survey known as the Andhra Pradesh Children and Parents Study (APCAPS, 2003-2005) of 1165 children aged 13 to 18 years from a controlled nutrition trial originally conducted in South India during the period of 1987 to 1990; and (2) nationally representative data from the India Human Development Survey (IHDS-2, 2011-2012) of 6121 children aged 6 to 12 years. Results: In APCAPS, children with >36 months of breastfeeding scored 0.28 (95% confidence interval [95% CI]: 0.00-0.56; P < .05) higher on tests than those with up to 12 months of breastfeeding. In the nationally representative IHDS-2 data, above-median breastfeeding duration was associated with 0.1 year (95% CI: 0.04-0.16; P < .01) higher educational attainment. In IHDS-2, >12 to 24 months and >24 months of breastfeeding were associated with 0.12 (95% CI: 0.01-0.23; P < .05) and 0.19 years of (95% CI: 0.05-0.34; P < .05) higher educational attainment, respectively, than for those with up to 6 months of breastfeeding. In additional analyses by sex, we found that the benefits of breastfeeding accrued primarily to boys. Conclusion: Breastfeeding duration was associated with small gains in educational outcomes for boys but not for girls in India.